St. Louis Paper - Zinc Mining at Franklin, N. J. (with Discussion) - C. M. Haight; B. F. Tillson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
I. General Remarks..........................723 1. Location............................723 2. Characteristics of the Orebody..................725 (a) Mineralogical (b) Shape, Strike, Dip, Size, Etc. (1) Ore (2) Country Rock 3. Historical Sketch........................725 11. Mining Method..........................726 1. Outline of Methods Now in Operation............... 726 (a) Stopes (b) Fill . (c) Pillars (d) Slices (e) Transportation (f) Miscellaneous 111. Mining Operations........................727 1. Shaft..............................727 (a) Sinking (b) Dimensions and Equipment, Sketches (1) Size, Inclination. Direction, Etc. (2) Timbering (3) Stations (4) Track (5) Hoisting Equipment (a) Skips (b) Engines and Ropes (c) Idlers (d) Man Cars (6) Loading Pockets (a) Operating Figures (7) Headframe